/- Copyright (c) 2017 Microsoft Corporation. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Mario Carneiro -/ import data.dlist import data.list.basic import data.seq.seq open function universes u v w /- coinductive wseq (α : Type u) : Type u | nil : wseq α | cons : α → wseq α → wseq α | think : wseq α → wseq α -/ /-- Weak sequences. While the `seq` structure allows for lists which may not be finite, a weak sequence also allows the computation of each element to involve an indeterminate amount of computation, including possibly an infinite loop. This is represented as a regular `seq` interspersed with `none` elements to indicate that computation is ongoing. This model is appropriate for Haskell style lazy lists, and is closed under most interesting computation patterns on infinite lists, but conversely it is difficult to extract elements from it. -/ def wseq (α) := seq (option α) namespace wseq variables {α : Type u} {β : Type v} {γ : Type w} /-- Turn a sequence into a weak sequence -/ def of_seq : seq α → wseq α := (<$>) some /-- Turn a list into a weak sequence -/ def of_list (l : list α) : wseq α := of_seq l /-- Turn a stream into a weak sequence -/ def of_stream (l : stream α) : wseq α := of_seq l instance coe_seq : has_coe (seq α) (wseq α) := ⟨of_seq⟩ instance coe_list : has_coe (list α) (wseq α) := ⟨of_list⟩ instance coe_stream : has_coe (stream α) (wseq α) := ⟨of_stream⟩ /-- The empty weak sequence -/ def nil : wseq α := seq.nil instance : inhabited (wseq α) := ⟨nil⟩ /-- Prepend an element to a weak sequence -/ def cons (a : α) : wseq α → wseq α := seq.cons (some a) /-- Compute for one tick, without producing any elements -/ def think : wseq α → wseq α := seq.cons none /-- Destruct a weak sequence, to (eventually possibly) produce either `none` for `nil` or `some (a, s)` if an element is produced. -/ def destruct : wseq α → computation (option (α × wseq α)) := computation.corec (λ s, match seq.destruct s with | none := sum.inl none | some (none, s') := sum.inr s' | some (some a, s') := sum.inl (some (a, s')) end) def cases_on {C : wseq α → Sort v} (s : wseq α) (h1 : C nil) (h2 : ∀ x s, C (cons x s)) (h3 : ∀ s, C (think s)) : C s := seq.cases_on s h1 (λ o, option.cases_on o h3 h2) protected def mem (a : α) (s : wseq α) := seq.mem (some a) s instance : has_mem α (wseq α) := ⟨wseq.mem⟩ theorem not_mem_nil (a : α) : a ∉ @nil α := seq.not_mem_nil a /-- Get the head of a weak sequence. This involves a possibly infinite computation. -/ def head (s : wseq α) : computation (option α) := computation.map ((<$>) prod.fst) (destruct s) /-- Encode a computation yielding a weak sequence into additional `think` constructors in a weak sequence -/ def flatten : computation (wseq α) → wseq α := seq.corec (λ c, match computation.destruct c with | sum.inl s := seq.omap return (seq.destruct s) | sum.inr c' := some (none, c') end) /-- Get the tail of a weak sequence. This doesn't need a `computation` wrapper, unlike `head`, because `flatten` allows us to hide this in the construction of the weak sequence itself. -/ def tail (s : wseq α) : wseq α := flatten $ (λ o, option.rec_on o nil prod.snd) <$> destruct s /-- drop the first `n` elements from `s`. -/ def drop (s : wseq α) : ℕ → wseq α | 0 := s | (n+1) := tail (drop n) attribute [simp] drop /-- Get the nth element of `s`. -/ def nth (s : wseq α) (n : ℕ) : computation (option α) := head (drop s n) /-- Convert `s` to a list (if it is finite and completes in finite time). -/ def to_list (s : wseq α) : computation (list α) := @computation.corec (list α) (list α × wseq α) (λ ⟨l, s⟩, match seq.destruct s with | none := sum.inl l.reverse | some (none, s') := sum.inr (l, s') | some (some a, s') := sum.inr (a::l, s') end) ([], s) /-- Get the length of `s` (if it is finite and completes in finite time). -/ def length (s : wseq α) : computation ℕ := @computation.corec ℕ (ℕ × wseq α) (λ ⟨n, s⟩, match seq.destruct s with | none := sum.inl n | some (none, s') := sum.inr (n, s') | some (some a, s') := sum.inr (n+1, s') end) (0, s) /-- A weak sequence is finite if `to_list s` terminates. Equivalently, it is a finite number of `think` and `cons` applied to `nil`. -/ class is_finite (s : wseq α) : Prop := (out : (to_list s).terminates) instance to_list_terminates (s : wseq α) [h : is_finite s] : (to_list s).terminates := h.out /-- Get the list corresponding to a finite weak sequence. -/ def get (s : wseq α) [is_finite s] : list α := (to_list s).get /-- A weak sequence is *productive* if it never stalls forever - there are always a finite number of `think`s between `cons` constructors. The sequence itself is allowed to be infinite though. -/ class productive (s : wseq α) : Prop := (nth_terminates : ∀ n, (nth s n).terminates) theorem productive_iff (s : wseq α) : productive s ↔ ∀ n, (nth s n).terminates := ⟨λ h, h.1, λ h, ⟨h⟩⟩ instance nth_terminates (s : wseq α) [h : productive s] : ∀ n, (nth s n).terminates := h.nth_terminates instance head_terminates (s : wseq α) [productive s] : (head s).terminates := s.nth_terminates 0 /-- Replace the `n`th element of `s` with `a`. -/ def update_nth (s : wseq α) (n : ℕ) (a : α) : wseq α := @seq.corec (option α) (ℕ × wseq α) (λ ⟨n, s⟩, match seq.destruct s, n with | none, n := none | some (none, s'), n := some (none, n, s') | some (some a', s'), 0 := some (some a', 0, s') | some (some a', s'), 1 := some (some a, 0, s') | some (some a', s'), (n+2) := some (some a', n+1, s') end) (n+1, s) /-- Remove the `n`th element of `s`. -/ def remove_nth (s : wseq α) (n : ℕ) : wseq α := @seq.corec (option α) (ℕ × wseq α) (λ ⟨n, s⟩, match seq.destruct s, n with | none, n := none | some (none, s'), n := some (none, n, s') | some (some a', s'), 0 := some (some a', 0, s') | some (some a', s'), 1 := some (none, 0, s') | some (some a', s'), (n+2) := some (some a', n+1, s') end) (n+1, s) /-- Map the elements of `s` over `f`, removing any values that yield `none`. -/ def filter_map (f : α → option β) : wseq α → wseq β := seq.corec (λ s, match seq.destruct s with | none := none | some (none, s') := some (none, s') | some (some a, s') := some (f a, s') end) /-- Select the elements of `s` that satisfy `p`. -/ def filter (p : α → Prop) [decidable_pred p] : wseq α → wseq α := filter_map (λ a, if p a then some a else none) -- example of infinite list manipulations /-- Get the first element of `s` satisfying `p`. -/ def find (p : α → Prop) [decidable_pred p] (s : wseq α) : computation (option α) := head $ filter p s /-- Zip a function over two weak sequences -/ def zip_with (f : α → β → γ) (s1 : wseq α) (s2 : wseq β) : wseq γ := @seq.corec (option γ) (wseq α × wseq β) (λ ⟨s1, s2⟩, match seq.destruct s1, seq.destruct s2 with | some (none, s1'), some (none, s2') := some (none, s1', s2') | some (some a1, s1'), some (none, s2') := some (none, s1, s2') | some (none, s1'), some (some a2, s2') := some (none, s1', s2) | some (some a1, s1'), some (some a2, s2') := some (some (f a1 a2), s1', s2') | _, _ := none end) (s1, s2) /-- Zip two weak sequences into a single sequence of pairs -/ def zip : wseq α → wseq β → wseq (α × β) := zip_with prod.mk /-- Get the list of indexes of elements of `s` satisfying `p` -/ def find_indexes (p : α → Prop) [decidable_pred p] (s : wseq α) : wseq ℕ := (zip s (stream.nats : wseq ℕ)).filter_map (λ ⟨a, n⟩, if p a then some n else none) /-- Get the index of the first element of `s` satisfying `p` -/ def find_index (p : α → Prop) [decidable_pred p] (s : wseq α) : computation ℕ := (λ o, option.get_or_else o 0) <$> head (find_indexes p s) /-- Get the index of the first occurrence of `a` in `s` -/ def index_of [decidable_eq α] (a : α) : wseq α → computation ℕ := find_index (eq a) /-- Get the indexes of occurrences of `a` in `s` -/ def indexes_of [decidable_eq α] (a : α) : wseq α → wseq ℕ := find_indexes (eq a) /-- `union s1 s2` is a weak sequence which interleaves `s1` and `s2` in some order (nondeterministically). -/ def union (s1 s2 : wseq α) : wseq α := @seq.corec (option α) (wseq α × wseq α) (λ ⟨s1, s2⟩, match seq.destruct s1, seq.destruct s2 with | none, none := none | some (a1, s1'), none := some (a1, s1', nil) | none, some (a2, s2') := some (a2, nil, s2') | some (none, s1'), some (none, s2') := some (none, s1', s2') | some (some a1, s1'), some (none, s2') := some (some a1, s1', s2') | some (none, s1'), some (some a2, s2') := some (some a2, s1', s2') | some (some a1, s1'), some (some a2, s2') := some (some a1, cons a2 s1', s2') end) (s1, s2) /-- Returns `tt` if `s` is `nil` and `ff` if `s` has an element -/ def is_empty (s : wseq α) : computation bool := computation.map option.is_none $ head s /-- Calculate one step of computation -/ def compute (s : wseq α) : wseq α := match seq.destruct s with | some (none, s') := s' | _ := s end /-- Get the first `n` elements of a weak sequence -/ def take (s : wseq α) (n : ℕ) : wseq α := @seq.corec (option α) (ℕ × wseq α) (λ ⟨n, s⟩, match n, seq.destruct s with | 0, _ := none | m+1, none := none | m+1, some (none, s') := some (none, m+1, s') | m+1, some (some a, s') := some (some a, m, s') end) (n, s) /-- Split the sequence at position `n` into a finite initial segment and the weak sequence tail -/ def split_at (s : wseq α) (n : ℕ) : computation (list α × wseq α) := @computation.corec (list α × wseq α) (ℕ × list α × wseq α) (λ ⟨n, l, s⟩, match n, seq.destruct s with | 0, _ := sum.inl (l.reverse, s) | m+1, none := sum.inl (l.reverse, s) | m+1, some (none, s') := sum.inr (n, l, s') | m+1, some (some a, s') := sum.inr (m, a::l, s') end) (n, [], s) /-- Returns `tt` if any element of `s` satisfies `p` -/ def any (s : wseq α) (p : α → bool) : computation bool := computation.corec (λ s : wseq α, match seq.destruct s with | none := sum.inl ff | some (none, s') := sum.inr s' | some (some a, s') := if p a then sum.inl tt else sum.inr s' end) s /-- Returns `tt` if every element of `s` satisfies `p` -/ def all (s : wseq α) (p : α → bool) : computation bool := computation.corec (λ s : wseq α, match seq.destruct s with | none := sum.inl tt | some (none, s') := sum.inr s' | some (some a, s') := if p a then sum.inr s' else sum.inl ff end) s /-- Apply a function to the elements of the sequence to produce a sequence of partial results. (There is no `scanr` because this would require working from the end of the sequence, which may not exist.) -/ def scanl (f : α → β → α) (a : α) (s : wseq β) : wseq α := cons a $ @seq.corec (option α) (α × wseq β) (λ ⟨a, s⟩, match seq.destruct s with | none := none | some (none, s') := some (none, a, s') | some (some b, s') := let a' := f a b in some (some a', a', s') end) (a, s) /-- Get the weak sequence of initial segments of the input sequence -/ def inits (s : wseq α) : wseq (list α) := cons [] $ @seq.corec (option (list α)) (dlist α × wseq α) (λ ⟨l, s⟩, match seq.destruct s with | none := none | some (none, s') := some (none, l, s') | some (some a, s') := let l' := l.concat a in some (some l'.to_list, l', s') end) (dlist.empty, s) /-- Like take, but does not wait for a result. Calculates `n` steps of computation and returns the sequence computed so far -/ def collect (s : wseq α) (n : ℕ) : list α := (seq.take n s).filter_map id /-- Append two weak sequences. As with `seq.append`, this may not use the second sequence if the first one takes forever to compute -/ def append : wseq α → wseq α → wseq α := seq.append /-- Map a function over a weak sequence -/ def map (f : α → β) : wseq α → wseq β := seq.map (option.map f) /-- Flatten a sequence of weak sequences. (Note that this allows empty sequences, unlike `seq.join`.) -/ def join (S : wseq (wseq α)) : wseq α := seq.join ((λ o : option (wseq α), match o with | none := seq1.ret none | some s := (none, s) end) <$> S) /-- Monadic bind operator for weak sequences -/ def bind (s : wseq α) (f : α → wseq β) : wseq β := join (map f s) @[simp] def lift_rel_o (R : α → β → Prop) (C : wseq α → wseq β → Prop) : option (α × wseq α) → option (β × wseq β) → Prop | none none := true | (some (a, s)) (some (b, t)) := R a b ∧ C s t | _ _ := false theorem lift_rel_o.imp {R S : α → β → Prop} {C D : wseq α → wseq β → Prop} (H1 : ∀ a b, R a b → S a b) (H2 : ∀ s t, C s t → D s t) : ∀ {o p}, lift_rel_o R C o p → lift_rel_o S D o p | none none h := trivial | (some (a, s)) (some (b, t)) h := and.imp (H1 _ _) (H2 _ _) h | none (some _) h := false.elim h | (some (_, _)) none h := false.elim h theorem lift_rel_o.imp_right (R : α → β → Prop) {C D : wseq α → wseq β → Prop} (H : ∀ s t, C s t → D s t) {o p} : lift_rel_o R C o p → lift_rel_o R D o p := lift_rel_o.imp (λ _ _, id) H @[simp] def bisim_o (R : wseq α → wseq α → Prop) : option (α × wseq α) → option (α × wseq α) → Prop := lift_rel_o (=) R theorem bisim_o.imp {R S : wseq α → wseq α → Prop} (H : ∀ s t, R s t → S s t) {o p} : bisim_o R o p → bisim_o S o p := lift_rel_o.imp_right _ H /-- Two weak sequences are `lift_rel R` related if they are either both empty, or they are both nonempty and the heads are `R` related and the tails are `lift_rel R` related. (This is a coinductive definition.) -/ def lift_rel (R : α → β → Prop) (s : wseq α) (t : wseq β) : Prop := ∃ C : wseq α → wseq β → Prop, C s t ∧ ∀ {s t}, C s t → computation.lift_rel (lift_rel_o R C) (destruct s) (destruct t) /-- If two sequences are equivalent, then they have the same values and the same computational behavior (i.e. if one loops forever then so does the other), although they may differ in the number of `think`s needed to arrive at the answer. -/ def equiv : wseq α → wseq α → Prop := lift_rel (=) theorem lift_rel_destruct {R : α → β → Prop} {s : wseq α} {t : wseq β} : lift_rel R s t → computation.lift_rel (lift_rel_o R (lift_rel R)) (destruct s) (destruct t) | ⟨R, h1, h2⟩ := by refine computation.lift_rel.imp _ _ _ (h2 h1); apply lift_rel_o.imp_right; exact λ s' t' h', ⟨R, h', @h2⟩ theorem lift_rel_destruct_iff {R : α → β → Prop} {s : wseq α} {t : wseq β} : lift_rel R s t ↔ computation.lift_rel (lift_rel_o R (lift_rel R)) (destruct s) (destruct t) := ⟨lift_rel_destruct, λ h, ⟨λ s t, lift_rel R s t ∨ computation.lift_rel (lift_rel_o R (lift_rel R)) (destruct s) (destruct t), or.inr h, λ s t h, begin have h : computation.lift_rel (lift_rel_o R (lift_rel R)) (destruct s) (destruct t), { cases h with h h, exact lift_rel_destruct h, assumption }, apply computation.lift_rel.imp _ _ _ h, intros a b, apply lift_rel_o.imp_right, intros s t, apply or.inl end⟩⟩ infix ` ~ `:50 := equiv theorem destruct_congr {s t : wseq α} : s ~ t → computation.lift_rel (bisim_o (~)) (destruct s) (destruct t) := lift_rel_destruct theorem destruct_congr_iff {s t : wseq α} : s ~ t ↔ computation.lift_rel (bisim_o (~)) (destruct s) (destruct t) := lift_rel_destruct_iff theorem lift_rel.refl (R : α → α → Prop) (H : reflexive R) : reflexive (lift_rel R) := λ s, begin refine ⟨(=), rfl, λ s t (h : s = t), _⟩, rw ←h, apply computation.lift_rel.refl, intro a, cases a with a, simp, cases a; simp, apply H end theorem lift_rel_o.swap (R : α → β → Prop) (C) : swap (lift_rel_o R C) = lift_rel_o (swap R) (swap C) := by funext x y; cases x with x; [skip, cases x]; { cases y with y; [skip, cases y]; refl } theorem lift_rel.swap_lem {R : α → β → Prop} {s1 s2} (h : lift_rel R s1 s2) : lift_rel (swap R) s2 s1 := begin refine ⟨swap (lift_rel R), h, λ s t (h : lift_rel R t s), _⟩, rw [←lift_rel_o.swap, computation.lift_rel.swap], apply lift_rel_destruct h end theorem lift_rel.swap (R : α → β → Prop) : swap (lift_rel R) = lift_rel (swap R) := funext $ λ x, funext $ λ y, propext ⟨lift_rel.swap_lem, lift_rel.swap_lem⟩ theorem lift_rel.symm (R : α → α → Prop) (H : symmetric R) : symmetric (lift_rel R) := λ s1 s2 (h : swap (lift_rel R) s2 s1), by rwa [lift_rel.swap, show swap R = R, from funext $ λ a, funext $ λ b, propext $ by constructor; apply H] at h theorem lift_rel.trans (R : α → α → Prop) (H : transitive R) : transitive (lift_rel R) := λ s t u h1 h2, begin refine ⟨λ s u, ∃ t, lift_rel R s t ∧ lift_rel R t u, ⟨t, h1, h2⟩, λ s u h, _⟩, rcases h with ⟨t, h1, h2⟩, have h1 := lift_rel_destruct h1, have h2 := lift_rel_destruct h2, refine computation.lift_rel_def.2 ⟨(computation.terminates_of_lift_rel h1).trans (computation.terminates_of_lift_rel h2), λ a c ha hc, _⟩, rcases h1.left ha with ⟨b, hb, t1⟩, have t2 := computation.rel_of_lift_rel h2 hb hc, cases a with a; cases c with c, { trivial }, { cases b, {cases t2}, {cases t1} }, { cases a, cases b with b, {cases t1}, {cases b, cases t2} }, { cases a with a s, cases b with b, {cases t1}, cases b with b t, cases c with c u, cases t1 with ab st, cases t2 with bc tu, exact ⟨H ab bc, t, st, tu⟩ } end theorem lift_rel.equiv (R : α → α → Prop) : equivalence R → equivalence (lift_rel R) | ⟨refl, symm, trans⟩ := ⟨lift_rel.refl R refl, lift_rel.symm R symm, lift_rel.trans R trans⟩ @[refl] theorem equiv.refl : ∀ (s : wseq α), s ~ s := lift_rel.refl (=) eq.refl @[symm] theorem equiv.symm : ∀ {s t : wseq α}, s ~ t → t ~ s := lift_rel.symm (=) (@eq.symm _) @[trans] theorem equiv.trans : ∀ {s t u : wseq α}, s ~ t → t ~ u → s ~ u := lift_rel.trans (=) (@eq.trans _) theorem equiv.equivalence : equivalence (@equiv α) := ⟨@equiv.refl _, @equiv.symm _, @equiv.trans _⟩ open computation local notation `return` := computation.return @[simp] theorem destruct_nil : destruct (nil : wseq α) = return none := computation.destruct_eq_ret rfl @[simp] theorem destruct_cons (a : α) (s) : destruct (cons a s) = return (some (a, s)) := computation.destruct_eq_ret $ by simp [destruct, cons, computation.rmap] @[simp] theorem destruct_think (s : wseq α) : destruct (think s) = (destruct s).think := computation.destruct_eq_think $ by simp [destruct, think, computation.rmap] @[simp] theorem seq_destruct_nil : seq.destruct (nil : wseq α) = none := seq.destruct_nil @[simp] theorem seq_destruct_cons (a : α) (s) : seq.destruct (cons a s) = some (some a, s) := seq.destruct_cons _ _ @[simp] theorem seq_destruct_think (s : wseq α) : seq.destruct (think s) = some (none, s) := seq.destruct_cons _ _ @[simp] theorem head_nil : head (nil : wseq α) = return none := by simp [head]; refl @[simp] theorem head_cons (a : α) (s) : head (cons a s) = return (some a) := by simp [head]; refl @[simp] theorem head_think (s : wseq α) : head (think s) = (head s).think := by simp [head]; refl @[simp] theorem flatten_ret (s : wseq α) : flatten (return s) = s := begin refine seq.eq_of_bisim (λ s1 s2, flatten (return s2) = s1) _ rfl, intros s' s h, rw ←h, simp [flatten], cases seq.destruct s, { simp }, { cases val with o s', simp } end @[simp] theorem flatten_think (c : computation (wseq α)) : flatten c.think = think (flatten c) := seq.destruct_eq_cons $ by simp [flatten, think] @[simp] theorem destruct_flatten (c : computation (wseq α)) : destruct (flatten c) = c >>= destruct := begin refine computation.eq_of_bisim (λ c1 c2, c1 = c2 ∨ ∃ c, c1 = destruct (flatten c) ∧ c2 = computation.bind c destruct) _ (or.inr ⟨c, rfl, rfl⟩), intros c1 c2 h, exact match c1, c2, h with | _, _, (or.inl $ eq.refl c) := by cases c.destruct; simp | _, _, (or.inr ⟨c, rfl, rfl⟩) := begin apply c.cases_on (λ a, _) (λ c', _); repeat {simp}, { cases (destruct a).destruct; simp }, { exact or.inr ⟨c', rfl, rfl⟩ } end end end theorem head_terminates_iff (s : wseq α) : terminates (head s) ↔ terminates (destruct s) := terminates_map_iff _ (destruct s) @[simp] theorem tail_nil : tail (nil : wseq α) = nil := by simp [tail] @[simp] theorem tail_cons (a : α) (s) : tail (cons a s) = s := by simp [tail] @[simp] theorem tail_think (s : wseq α) : tail (think s) = (tail s).think := by simp [tail] @[simp] theorem dropn_nil (n) : drop (nil : wseq α) n = nil := by induction n; simp [*, drop] @[simp] theorem dropn_cons (a : α) (s) (n) : drop (cons a s) (n+1) = drop s n := by induction n; simp [*, drop] @[simp] theorem dropn_think (s : wseq α) (n) : drop (think s) n = (drop s n).think := by induction n; simp [*, drop] theorem dropn_add (s : wseq α) (m) : ∀ n, drop s (m + n) = drop (drop s m) n | 0 := rfl | (n+1) := congr_arg tail (dropn_add n) theorem dropn_tail (s : wseq α) (n) : drop (tail s) n = drop s (n + 1) := by rw add_comm; symmetry; apply dropn_add theorem nth_add (s : wseq α) (m n) : nth s (m + n) = nth (drop s m) n := congr_arg head (dropn_add _ _ _) theorem nth_tail (s : wseq α) (n) : nth (tail s) n = nth s (n + 1) := congr_arg head (dropn_tail _ _) @[simp] theorem join_nil : join nil = (nil : wseq α) := seq.join_nil @[simp] theorem join_think (S : wseq (wseq α)) : join (think S) = think (join S) := by { simp [think, join], unfold functor.map, simp [join, seq1.ret] } @[simp] theorem join_cons (s : wseq α) (S) : join (cons s S) = think (append s (join S)) := by { simp [think, join], unfold functor.map, simp [join, cons, append] } @[simp] theorem nil_append (s : wseq α) : append nil s = s := seq.nil_append _ @[simp] theorem cons_append (a : α) (s t) : append (cons a s) t = cons a (append s t) := seq.cons_append _ _ _ @[simp] theorem think_append (s t : wseq α) : append (think s) t = think (append s t) := seq.cons_append _ _ _ @[simp] theorem append_nil (s : wseq α) : append s nil = s := seq.append_nil _ @[simp] theorem append_assoc (s t u : wseq α) : append (append s t) u = append s (append t u) := seq.append_assoc _ _ _ @[simp] def tail.aux : option (α × wseq α) → computation (option (α × wseq α)) | none := return none | (some (a, s)) := destruct s theorem destruct_tail (s : wseq α) : destruct (tail s) = destruct s >>= tail.aux := begin simp [tail], rw [← bind_pure_comp_eq_map, is_lawful_monad.bind_assoc], apply congr_arg, ext1 (_|⟨a, s⟩); apply (@pure_bind computation _ _ _ _ _ _).trans _; simp end @[simp] def drop.aux : ℕ → option (α × wseq α) → computation (option (α × wseq α)) | 0 := return | (n+1) := λ a, tail.aux a >>= drop.aux n theorem drop.aux_none : ∀ n, @drop.aux α n none = return none | 0 := rfl | (n+1) := show computation.bind (return none) (drop.aux n) = return none, by rw [ret_bind, drop.aux_none] theorem destruct_dropn : ∀ (s : wseq α) n, destruct (drop s n) = destruct s >>= drop.aux n | s 0 := (bind_ret' _).symm | s (n+1) := by rw [← dropn_tail, destruct_dropn _ n, destruct_tail, is_lawful_monad.bind_assoc]; refl theorem head_terminates_of_head_tail_terminates (s : wseq α) [T : terminates (head (tail s))] : terminates (head s) := (head_terminates_iff _).2 $ begin rcases (head_terminates_iff _).1 T with ⟨⟨a, h⟩⟩, simp [tail] at h, rcases exists_of_mem_bind h with ⟨s', h1, h2⟩, unfold functor.map at h1, exact let ⟨t, h3, h4⟩ := exists_of_mem_map h1 in terminates_of_mem h3 end theorem destruct_some_of_destruct_tail_some {s : wseq α} {a} (h : some a ∈ destruct (tail s)) : ∃ a', some a' ∈ destruct s := begin unfold tail functor.map at h, simp at h, rcases exists_of_mem_bind h with ⟨t, tm, td⟩, clear h, rcases exists_of_mem_map tm with ⟨t', ht', ht2⟩, clear tm, cases t' with t'; rw ←ht2 at td; simp at td, { have := mem_unique td (ret_mem _), contradiction }, { exact ⟨_, ht'⟩ } end theorem head_some_of_head_tail_some {s : wseq α} {a} (h : some a ∈ head (tail s)) : ∃ a', some a' ∈ head s := begin unfold head at h, rcases exists_of_mem_map h with ⟨o, md, e⟩, clear h, cases o with o; injection e with h', clear e h', cases destruct_some_of_destruct_tail_some md with a am, exact ⟨_, mem_map ((<$>) (@prod.fst α (wseq α))) am⟩ end theorem head_some_of_nth_some {s : wseq α} {a n} (h : some a ∈ nth s n) : ∃ a', some a' ∈ head s := begin revert a, induction n with n IH; intros, exacts [⟨_, h⟩, let ⟨a', h'⟩ := head_some_of_head_tail_some h in IH h'] end instance productive_tail (s : wseq α) [productive s] : productive (tail s) := ⟨λ n, by rw [nth_tail]; apply_instance⟩ instance productive_dropn (s : wseq α) [productive s] (n) : productive (drop s n) := ⟨λ m, by rw [←nth_add]; apply_instance⟩ /-- Given a productive weak sequence, we can collapse all the `think`s to produce a sequence. -/ def to_seq (s : wseq α) [productive s] : seq α := ⟨λ n, (nth s n).get, λ n h, begin cases e : computation.get (nth s (n + 1)), {assumption}, have := mem_of_get_eq _ e, simp [nth] at this h, cases head_some_of_head_tail_some this with a' h', have := mem_unique h' (@mem_of_get_eq _ _ _ _ h), contradiction end⟩ theorem nth_terminates_le {s : wseq α} {m n} (h : m ≤ n) : terminates (nth s n) → terminates (nth s m) := by induction h with m' h IH; [exact id, exact λ T, IH (@head_terminates_of_head_tail_terminates _ _ T)] theorem head_terminates_of_nth_terminates {s : wseq α} {n} : terminates (nth s n) → terminates (head s) := nth_terminates_le (nat.zero_le n) theorem destruct_terminates_of_nth_terminates {s : wseq α} {n} (T : terminates (nth s n)) : terminates (destruct s) := (head_terminates_iff _).1 $ head_terminates_of_nth_terminates T theorem mem_rec_on {C : wseq α → Prop} {a s} (M : a ∈ s) (h1 : ∀ b s', (a = b ∨ C s') → C (cons b s')) (h2 : ∀ s, C s → C (think s)) : C s := begin apply seq.mem_rec_on M, intros o s' h, cases o with b, { apply h2, cases h, {contradiction}, {assumption} }, { apply h1, apply or.imp_left _ h, intro h, injection h } end @[simp] theorem mem_think (s : wseq α) (a) : a ∈ think s ↔ a ∈ s := begin cases s with f al, change some (some a) ∈ some none :: f ↔ some (some a) ∈ f, constructor; intro h, { apply (stream.eq_or_mem_of_mem_cons h).resolve_left, intro, injections }, { apply stream.mem_cons_of_mem _ h } end theorem eq_or_mem_iff_mem {s : wseq α} {a a' s'} : some (a', s') ∈ destruct s → (a ∈ s ↔ a = a' ∨ a ∈ s') := begin generalize e : destruct s = c, intro h, revert s, apply computation.mem_rec_on h _ (λ c IH, _); intro s; apply s.cases_on _ (λ x s, _) (λ s, _); intros m; have := congr_arg computation.destruct m; simp at this; cases this with i1 i2, { rw [i1, i2], cases s' with f al, unfold cons has_mem.mem wseq.mem seq.mem seq.cons, simp, have h_a_eq_a' : a = a' ↔ some (some a) = some (some a'), {simp}, rw [h_a_eq_a'], refine ⟨stream.eq_or_mem_of_mem_cons, λ o, _⟩, { cases o with e m, { rw e, apply stream.mem_cons }, { exact stream.mem_cons_of_mem _ m } } }, { simp, exact IH this } end @[simp] theorem mem_cons_iff (s : wseq α) (b) {a} : a ∈ cons b s ↔ a = b ∨ a ∈ s := eq_or_mem_iff_mem $ by simp [ret_mem] theorem mem_cons_of_mem {s : wseq α} (b) {a} (h : a ∈ s) : a ∈ cons b s := (mem_cons_iff _ _).2 (or.inr h) theorem mem_cons (s : wseq α) (a) : a ∈ cons a s := (mem_cons_iff _ _).2 (or.inl rfl) theorem mem_of_mem_tail {s : wseq α} {a} : a ∈ tail s → a ∈ s := begin intro h, have := h, cases h with n e, revert s, simp [stream.nth], induction n with n IH; intro s; apply s.cases_on _ (λ x s, _) (λ s, _); repeat{simp}; intros m e; injections, { exact or.inr m }, { exact or.inr m }, { apply IH m, rw e, cases tail s, refl } end theorem mem_of_mem_dropn {s : wseq α} {a} : ∀ {n}, a ∈ drop s n → a ∈ s | 0 h := h | (n+1) h := @mem_of_mem_dropn n (mem_of_mem_tail h) theorem nth_mem {s : wseq α} {a n} : some a ∈ nth s n → a ∈ s := begin revert s, induction n with n IH; intros s h, { rcases exists_of_mem_map h with ⟨o, h1, h2⟩, cases o with o; injection h2 with h', cases o with a' s', exact (eq_or_mem_iff_mem h1).2 (or.inl h'.symm) }, { have := @IH (tail s), rw nth_tail at this, exact mem_of_mem_tail (this h) } end theorem exists_nth_of_mem {s : wseq α} {a} (h : a ∈ s) : ∃ n, some a ∈ nth s n := begin apply mem_rec_on h, { intros a' s' h, cases h with h h, { existsi 0, simp [nth], rw h, apply ret_mem }, { cases h with n h, existsi n+1, simp [nth], exact h } }, { intros s' h, cases h with n h, existsi n, simp [nth], apply think_mem h } end theorem exists_dropn_of_mem {s : wseq α} {a} (h : a ∈ s) : ∃ n s', some (a, s') ∈ destruct (drop s n) := let ⟨n, h⟩ := exists_nth_of_mem h in ⟨n, begin rcases (head_terminates_iff _).1 ⟨⟨_, h⟩⟩ with ⟨⟨o, om⟩⟩, have := mem_unique (mem_map _ om) h, cases o with o; injection this with i, cases o with a' s', dsimp at i, rw i at om, exact ⟨_, om⟩ end⟩ theorem lift_rel_dropn_destruct {R : α → β → Prop} {s t} (H : lift_rel R s t) : ∀ n, computation.lift_rel (lift_rel_o R (lift_rel R)) (destruct (drop s n)) (destruct (drop t n)) | 0 := lift_rel_destruct H | (n+1) := begin simp [destruct_tail], apply lift_rel_bind, apply lift_rel_dropn_destruct n, exact λ a b o, match a, b, o with | none, none, _ := by simp | some (a, s), some (b, t), ⟨h1, h2⟩ := by simp [tail.aux]; apply lift_rel_destruct h2 end end theorem exists_of_lift_rel_left {R : α → β → Prop} {s t} (H : lift_rel R s t) {a} (h : a ∈ s) : ∃ {b}, b ∈ t ∧ R a b := let ⟨n, h⟩ := exists_nth_of_mem h, ⟨some (._, s'), sd, rfl⟩ := exists_of_mem_map h, ⟨some (b, t'), td, ⟨ab, _⟩⟩ := (lift_rel_dropn_destruct H n).left sd in ⟨b, nth_mem (mem_map ((<$>) prod.fst.{v v}) td), ab⟩ theorem exists_of_lift_rel_right {R : α → β → Prop} {s t} (H : lift_rel R s t) {b} (h : b ∈ t) : ∃ {a}, a ∈ s ∧ R a b := by rw ←lift_rel.swap at H; exact exists_of_lift_rel_left H h theorem head_terminates_of_mem {s : wseq α} {a} (h : a ∈ s) : terminates (head s) := let ⟨n, h⟩ := exists_nth_of_mem h in head_terminates_of_nth_terminates ⟨⟨_, h⟩⟩ theorem of_mem_append {s₁ s₂ : wseq α} {a : α} : a ∈ append s₁ s₂ → a ∈ s₁ ∨ a ∈ s₂ := seq.of_mem_append theorem mem_append_left {s₁ s₂ : wseq α} {a : α} : a ∈ s₁ → a ∈ append s₁ s₂ := seq.mem_append_left theorem exists_of_mem_map {f} {b : β} : ∀ {s : wseq α}, b ∈ map f s → ∃ a, a ∈ s ∧ f a = b | ⟨g, al⟩ h := let ⟨o, om, oe⟩ := seq.exists_of_mem_map h in by cases o with a; injection oe with h'; exact ⟨a, om, h'⟩ @[simp] theorem lift_rel_nil (R : α → β → Prop) : lift_rel R nil nil := by rw [lift_rel_destruct_iff]; simp @[simp] theorem lift_rel_cons (R : α → β → Prop) (a b s t) : lift_rel R (cons a s) (cons b t) ↔ R a b ∧ lift_rel R s t := by rw [lift_rel_destruct_iff]; simp @[simp] theorem lift_rel_think_left (R : α → β → Prop) (s t) : lift_rel R (think s) t ↔ lift_rel R s t := by rw [lift_rel_destruct_iff, lift_rel_destruct_iff]; simp @[simp] theorem lift_rel_think_right (R : α → β → Prop) (s t) : lift_rel R s (think t) ↔ lift_rel R s t := by rw [lift_rel_destruct_iff, lift_rel_destruct_iff]; simp theorem cons_congr {s t : wseq α} (a : α) (h : s ~ t) : cons a s ~ cons a t := by unfold equiv; simp; exact h theorem think_equiv (s : wseq α) : think s ~ s := by unfold equiv; simp; apply equiv.refl theorem think_congr {s t : wseq α} (a : α) (h : s ~ t) : think s ~ think t := by unfold equiv; simp; exact h theorem head_congr : ∀ {s t : wseq α}, s ~ t → head s ~ head t := suffices ∀ {s t : wseq α}, s ~ t → ∀ {o}, o ∈ head s → o ∈ head t, from λ s t h o, ⟨this h, this h.symm⟩, begin intros s t h o ho, rcases @computation.exists_of_mem_map _ _ _ _ (destruct s) ho with ⟨ds, dsm, dse⟩, rw ←dse, cases destruct_congr h with l r, rcases l dsm with ⟨dt, dtm, dst⟩, cases ds with a; cases dt with b, { apply mem_map _ dtm }, { cases b, cases dst }, { cases a, cases dst }, { cases a with a s', cases b with b t', rw dst.left, exact @mem_map _ _ (@functor.map _ _ (α × wseq α) _ prod.fst) _ (destruct t) dtm } end theorem flatten_equiv {c : computation (wseq α)} {s} (h : s ∈ c) : flatten c ~ s := begin apply computation.mem_rec_on h, { simp }, { intro s', apply equiv.trans, simp [think_equiv] } end theorem lift_rel_flatten {R : α → β → Prop} {c1 : computation (wseq α)} {c2 : computation (wseq β)} (h : c1.lift_rel (lift_rel R) c2) : lift_rel R (flatten c1) (flatten c2) := let S := λ s t, ∃ c1 c2, s = flatten c1 ∧ t = flatten c2 ∧ computation.lift_rel (lift_rel R) c1 c2 in ⟨S, ⟨c1, c2, rfl, rfl, h⟩, λ s t h, match s, t, h with ._, ._, ⟨c1, c2, rfl, rfl, h⟩ := begin simp, apply lift_rel_bind _ _ h, intros a b ab, apply computation.lift_rel.imp _ _ _ (lift_rel_destruct ab), intros a b, apply lift_rel_o.imp_right, intros s t h, refine ⟨return s, return t, _, _, _⟩; simp [h] end end⟩ theorem flatten_congr {c1 c2 : computation (wseq α)} : computation.lift_rel equiv c1 c2 → flatten c1 ~ flatten c2 := lift_rel_flatten theorem tail_congr {s t : wseq α} (h : s ~ t) : tail s ~ tail t := begin apply flatten_congr, unfold functor.map, rw [←bind_ret, ←bind_ret], apply lift_rel_bind _ _ (destruct_congr h), intros a b h, simp, cases a with a; cases b with b, { trivial }, { cases h }, { cases a, cases h }, { cases a with a s', cases b with b t', exact h.right } end theorem dropn_congr {s t : wseq α} (h : s ~ t) (n) : drop s n ~ drop t n := by induction n; simp [*, tail_congr] theorem nth_congr {s t : wseq α} (h : s ~ t) (n) : nth s n ~ nth t n := head_congr (dropn_congr h _) theorem mem_congr {s t : wseq α} (h : s ~ t) (a) : a ∈ s ↔ a ∈ t := suffices ∀ {s t : wseq α}, s ~ t → a ∈ s → a ∈ t, from ⟨this h, this h.symm⟩, λ s t h as, let ⟨n, hn⟩ := exists_nth_of_mem as in nth_mem ((nth_congr h _ _).1 hn) theorem productive_congr {s t : wseq α} (h : s ~ t) : productive s ↔ productive t := by simp only [productive_iff]; exact forall_congr (λ n, terminates_congr $ nth_congr h _) theorem equiv.ext {s t : wseq α} (h : ∀ n, nth s n ~ nth t n) : s ~ t := ⟨λ s t, ∀ n, nth s n ~ nth t n, h, λ s t h, begin refine lift_rel_def.2 ⟨_, _⟩, { rw [←head_terminates_iff, ←head_terminates_iff], exact terminates_congr (h 0) }, { intros a b ma mb, cases a with a; cases b with b, { trivial }, { injection mem_unique (mem_map _ ma) ((h 0 _).2 (mem_map _ mb)) }, { injection mem_unique (mem_map _ ma) ((h 0 _).2 (mem_map _ mb)) }, { cases a with a s', cases b with b t', injection mem_unique (mem_map _ ma) ((h 0 _).2 (mem_map _ mb)) with ab, refine ⟨ab, λ n, _⟩, refine (nth_congr (flatten_equiv (mem_map _ ma)) n).symm.trans ((_ : nth (tail s) n ~ nth (tail t) n).trans (nth_congr (flatten_equiv (mem_map _ mb)) n)), rw [nth_tail, nth_tail], apply h } } end⟩ theorem length_eq_map (s : wseq α) : length s = computation.map list.length (to_list s) := begin refine eq_of_bisim (λ c1 c2, ∃ (l : list α) (s : wseq α), c1 = corec length._match_2 (l.length, s) ∧ c2 = computation.map list.length (corec to_list._match_2 (l, s))) _ ⟨[], s, rfl, rfl⟩, intros s1 s2 h, rcases h with ⟨l, s, h⟩, rw [h.left, h.right], apply s.cases_on _ (λ a s, _) (λ s, _); repeat {simp [to_list, nil, cons, think, length]}, { refine ⟨a::l, s, _, _⟩; simp }, { refine ⟨l, s, _, _⟩; simp } end @[simp] theorem of_list_nil : of_list [] = (nil : wseq α) := rfl @[simp] theorem of_list_cons (a : α) (l) : of_list (a :: l) = cons a (of_list l) := show seq.map some (seq.of_list (a :: l)) = seq.cons (some a) (seq.map some (seq.of_list l)), by simp @[simp] theorem to_list'_nil (l : list α) : corec to_list._match_2 (l, nil) = return l.reverse := destruct_eq_ret rfl @[simp] theorem to_list'_cons (l : list α) (s : wseq α) (a : α) : corec to_list._match_2 (l, cons a s) = (corec to_list._match_2 (a::l, s)).think := destruct_eq_think $ by simp [to_list, cons] @[simp] theorem to_list'_think (l : list α) (s : wseq α) : corec to_list._match_2 (l, think s) = (corec to_list._match_2 (l, s)).think := destruct_eq_think $ by simp [to_list, think] theorem to_list'_map (l : list α) (s : wseq α) : corec to_list._match_2 (l, s) = ((++) l.reverse) <$> to_list s := begin refine eq_of_bisim (λ c1 c2, ∃ (l' : list α) (s : wseq α), c1 = corec to_list._match_2 (l' ++ l, s) ∧ c2 = computation.map ((++) l.reverse) (corec to_list._match_2 (l', s))) _ ⟨[], s, rfl, rfl⟩, intros s1 s2 h, rcases h with ⟨l', s, h⟩, rw [h.left, h.right], apply s.cases_on _ (λ a s, _) (λ s, _); repeat {simp [to_list, nil, cons, think, length]}, { refine ⟨a::l', s, _, _⟩; simp }, { refine ⟨l', s, _, _⟩; simp } end @[simp] theorem to_list_cons (a : α) (s) : to_list (cons a s) = (list.cons a <$> to_list s).think := destruct_eq_think $ by unfold to_list; simp; rw to_list'_map; simp; refl @[simp] theorem to_list_nil : to_list (nil : wseq α) = return [] := destruct_eq_ret rfl theorem to_list_of_list (l : list α) : l ∈ to_list (of_list l) := by induction l with a l IH; simp [ret_mem]; exact think_mem (mem_map _ IH) @[simp] theorem destruct_of_seq (s : seq α) : destruct (of_seq s) = return (s.head.map $ λ a, (a, of_seq s.tail)) := destruct_eq_ret $ begin simp [of_seq, head, destruct, seq.destruct, seq.head], rw [show seq.nth (some <$> s) 0 = some <$> seq.nth s 0, by apply seq.map_nth], cases seq.nth s 0 with a, { refl }, unfold functor.map, simp [destruct] end @[simp] theorem head_of_seq (s : seq α) : head (of_seq s) = return s.head := by simp [head]; cases seq.head s; refl @[simp] theorem tail_of_seq (s : seq α) : tail (of_seq s) = of_seq s.tail := begin simp [tail], apply s.cases_on _ (λ x s, _); simp [of_seq], {refl}, rw [seq.head_cons, seq.tail_cons], refl end @[simp] theorem dropn_of_seq (s : seq α) : ∀ n, drop (of_seq s) n = of_seq (s.drop n) | 0 := rfl | (n+1) := by dsimp [drop]; rw [dropn_of_seq, tail_of_seq] theorem nth_of_seq (s : seq α) (n) : nth (of_seq s) n = return (seq.nth s n) := by dsimp [nth]; rw [dropn_of_seq, head_of_seq, seq.head_dropn] instance productive_of_seq (s : seq α) : productive (of_seq s) := ⟨λ n, by rw nth_of_seq; apply_instance⟩ theorem to_seq_of_seq (s : seq α) : to_seq (of_seq s) = s := begin apply subtype.eq, funext n, dsimp [to_seq], apply get_eq_of_mem, rw nth_of_seq, apply ret_mem end /-- The monadic `return a` is a singleton list containing `a`. -/ def ret (a : α) : wseq α := of_list [a] @[simp] theorem map_nil (f : α → β) : map f nil = nil := rfl @[simp] theorem map_cons (f : α → β) (a s) : map f (cons a s) = cons (f a) (map f s) := seq.map_cons _ _ _ @[simp] theorem map_think (f : α → β) (s) : map f (think s) = think (map f s) := seq.map_cons _ _ _ @[simp] theorem map_id (s : wseq α) : map id s = s := by simp [map] @[simp] theorem map_ret (f : α → β) (a) : map f (ret a) = ret (f a) := by simp [ret] @[simp] theorem map_append (f : α → β) (s t) : map f (append s t) = append (map f s) (map f t) := seq.map_append _ _ _ theorem map_comp (f : α → β) (g : β → γ) (s : wseq α) : map (g ∘ f) s = map g (map f s) := begin dsimp [map], rw ←seq.map_comp, apply congr_fun, apply congr_arg, ext ⟨⟩; refl end theorem mem_map (f : α → β) {a : α} {s : wseq α} : a ∈ s → f a ∈ map f s := seq.mem_map (option.map f) -- The converse is not true without additional assumptions theorem exists_of_mem_join {a : α} : ∀ {S : wseq (wseq α)}, a ∈ join S → ∃ s, s ∈ S ∧ a ∈ s := suffices ∀ ss : wseq α, a ∈ ss → ∀ s S, append s (join S) = ss → a ∈ append s (join S) → a ∈ s ∨ ∃ s, s ∈ S ∧ a ∈ s, from λ S h, (this _ h nil S (by simp) (by simp [h])).resolve_left (not_mem_nil _), begin intros ss h, apply mem_rec_on h (λ b ss o, _) (λ ss IH, _); intros s S, { refine s.cases_on (S.cases_on _ (λ s S, _) (λ S, _)) (λ b' s, _) (λ s, _); intros ej m; simp at ej; have := congr_arg seq.destruct ej; simp at this; try {cases this}; try {contradiction}, substs b' ss, simp at m ⊢, cases o with e IH, { simp [e] }, cases m with e m, { simp [e] }, exact or.imp_left or.inr (IH _ _ rfl m) }, { refine s.cases_on (S.cases_on _ (λ s S, _) (λ S, _)) (λ b' s, _) (λ s, _); intros ej m; simp at ej; have := congr_arg seq.destruct ej; simp at this; try { try {have := this.1}, contradiction }; subst ss, { apply or.inr, simp at m ⊢, cases IH s S rfl m with as ex, { exact ⟨s, or.inl rfl, as⟩ }, { rcases ex with ⟨s', sS, as⟩, exact ⟨s', or.inr sS, as⟩ } }, { apply or.inr, simp at m, rcases (IH nil S (by simp) (by simp [m])).resolve_left (not_mem_nil _) with ⟨s, sS, as⟩, exact ⟨s, by simp [sS], as⟩ }, { simp at m IH ⊢, apply IH _ _ rfl m } } end theorem exists_of_mem_bind {s : wseq α} {f : α → wseq β} {b} (h : b ∈ bind s f) : ∃ a ∈ s, b ∈ f a := let ⟨t, tm, bt⟩ := exists_of_mem_join h, ⟨a, as, e⟩ := exists_of_mem_map tm in ⟨a, as, by rwa e⟩ theorem destruct_map (f : α → β) (s : wseq α) : destruct (map f s) = computation.map (option.map (prod.map f (map f))) (destruct s) := begin apply eq_of_bisim (λ c1 c2, ∃ s, c1 = destruct (map f s) ∧ c2 = computation.map (option.map (prod.map f (map f))) (destruct s)), { intros c1 c2 h, cases h with s h, rw [h.left, h.right], apply s.cases_on _ (λ a s, _) (λ s, _); simp, exact ⟨s, rfl, rfl⟩ }, { exact ⟨s, rfl, rfl⟩ } end theorem lift_rel_map {δ} (R : α → β → Prop) (S : γ → δ → Prop) {s1 : wseq α} {s2 : wseq β} {f1 : α → γ} {f2 : β → δ} (h1 : lift_rel R s1 s2) (h2 : ∀ {a b}, R a b → S (f1 a) (f2 b)) : lift_rel S (map f1 s1) (map f2 s2) := ⟨λ s1 s2, ∃ s t, s1 = map f1 s ∧ s2 = map f2 t ∧ lift_rel R s t, ⟨s1, s2, rfl, rfl, h1⟩, λ s1 s2 h, match s1, s2, h with ._, ._, ⟨s, t, rfl, rfl, h⟩ := begin simp [destruct_map], apply computation.lift_rel_map _ _ (lift_rel_destruct h), intros o p h, cases o with a; cases p with b; simp, { cases b; cases h }, { cases a; cases h }, { cases a with a s; cases b with b t, cases h with r h, exact ⟨h2 r, s, rfl, t, rfl, h⟩ } end end⟩ theorem map_congr (f : α → β) {s t : wseq α} (h : s ~ t) : map f s ~ map f t := lift_rel_map _ _ h (λ _ _, congr_arg _) @[simp] def destruct_append.aux (t : wseq α) : option (α × wseq α) → computation (option (α × wseq α)) | none := destruct t | (some (a, s)) := return (some (a, append s t)) theorem destruct_append (s t : wseq α) : destruct (append s t) = (destruct s).bind (destruct_append.aux t) := begin apply eq_of_bisim (λ c1 c2, ∃ s t, c1 = destruct (append s t) ∧ c2 = (destruct s).bind (destruct_append.aux t)) _ ⟨s, t, rfl, rfl⟩, intros c1 c2 h, rcases h with ⟨s, t, h⟩, rw [h.left, h.right], apply s.cases_on _ (λ a s, _) (λ s, _); simp, { apply t.cases_on _ (λ b t, _) (λ t, _); simp, { refine ⟨nil, t, _, _⟩; simp } }, { exact ⟨s, t, rfl, rfl⟩ } end @[simp] def destruct_join.aux : option (wseq α × wseq (wseq α)) → computation (option (α × wseq α)) | none := return none | (some (s, S)) := (destruct (append s (join S))).think theorem destruct_join (S : wseq (wseq α)) : destruct (join S) = (destruct S).bind destruct_join.aux := begin apply eq_of_bisim (λ c1 c2, c1 = c2 ∨ ∃ S, c1 = destruct (join S) ∧ c2 = (destruct S).bind destruct_join.aux) _ (or.inr ⟨S, rfl, rfl⟩), intros c1 c2 h, exact match c1, c2, h with | _, _, (or.inl $ eq.refl c) := by cases c.destruct; simp | _, _, or.inr ⟨S, rfl, rfl⟩ := begin apply S.cases_on _ (λ s S, _) (λ S, _); simp, { refine or.inr ⟨S, rfl, rfl⟩ } end end end theorem lift_rel_append (R : α → β → Prop) {s1 s2 : wseq α} {t1 t2 : wseq β} (h1 : lift_rel R s1 t1) (h2 : lift_rel R s2 t2) : lift_rel R (append s1 s2) (append t1 t2) := ⟨λ s t, lift_rel R s t ∨ ∃ s1 t1, s = append s1 s2 ∧ t = append t1 t2 ∧ lift_rel R s1 t1, or.inr ⟨s1, t1, rfl, rfl, h1⟩, λ s t h, match s, t, h with | s, t, or.inl h := begin apply computation.lift_rel.imp _ _ _ (lift_rel_destruct h), intros a b, apply lift_rel_o.imp_right, intros s t, apply or.inl end | ._, ._, or.inr ⟨s1, t1, rfl, rfl, h⟩ := begin simp [destruct_append], apply computation.lift_rel_bind _ _ (lift_rel_destruct h), intros o p h, cases o with a; cases p with b, { simp, apply computation.lift_rel.imp _ _ _ (lift_rel_destruct h2), intros a b, apply lift_rel_o.imp_right, intros s t, apply or.inl }, { cases b; cases h }, { cases a; cases h }, { cases a with a s; cases b with b t, cases h with r h, simp, exact ⟨r, or.inr ⟨s, rfl, t, rfl, h⟩⟩ } end end⟩ theorem lift_rel_join.lem (R : α → β → Prop) {S T} {U : wseq α → wseq β → Prop} (ST : lift_rel (lift_rel R) S T) (HU : ∀ s1 s2, (∃ s t S T, s1 = append s (join S) ∧ s2 = append t (join T) ∧ lift_rel R s t ∧ lift_rel (lift_rel R) S T) → U s1 s2) {a} (ma : a ∈ destruct (join S)) : ∃ {b}, b ∈ destruct (join T) ∧ lift_rel_o R U a b := begin cases exists_results_of_mem ma with n h, clear ma, revert a S T, apply nat.strong_induction_on n _, intros n IH a S T ST ra, simp [destruct_join] at ra, exact let ⟨o, m, k, rs1, rs2, en⟩ := of_results_bind ra, ⟨p, mT, rop⟩ := computation.exists_of_lift_rel_left (lift_rel_destruct ST) rs1.mem in by exact match o, p, rop, rs1, rs2, mT with | none, none, _, rs1, rs2, mT := by simp only [destruct_join]; exact ⟨none, mem_bind mT (ret_mem _), by rw eq_of_ret_mem rs2.mem; trivial⟩ | some (s, S'), some (t, T'), ⟨st, ST'⟩, rs1, rs2, mT := by simp [destruct_append] at rs2; exact let ⟨k1, rs3, ek⟩ := of_results_think rs2, ⟨o', m1, n1, rs4, rs5, ek1⟩ := of_results_bind rs3, ⟨p', mt, rop'⟩ := computation.exists_of_lift_rel_left (lift_rel_destruct st) rs4.mem in by exact match o', p', rop', rs4, rs5, mt with | none, none, _, rs4, rs5', mt := have n1 < n, begin rw [en, ek, ek1], apply lt_of_lt_of_le _ (nat.le_add_right _ _), apply nat.lt_succ_of_le (nat.le_add_right _ _) end, let ⟨ob, mb, rob⟩ := IH _ this ST' rs5' in by refine ⟨ob, _, rob⟩; { simp [destruct_join], apply mem_bind mT, simp [destruct_append], apply think_mem, apply mem_bind mt, exact mb } | some (a, s'), some (b, t'), ⟨ab, st'⟩, rs4, rs5, mt := begin simp at rs5, refine ⟨some (b, append t' (join T')), _, _⟩, { simp [destruct_join], apply mem_bind mT, simp [destruct_append], apply think_mem, apply mem_bind mt, apply ret_mem }, rw eq_of_ret_mem rs5.mem, exact ⟨ab, HU _ _ ⟨s', t', S', T', rfl, rfl, st', ST'⟩⟩ end end end end theorem lift_rel_join (R : α → β → Prop) {S : wseq (wseq α)} {T : wseq (wseq β)} (h : lift_rel (lift_rel R) S T) : lift_rel R (join S) (join T) := ⟨λ s1 s2, ∃ s t S T, s1 = append s (join S) ∧ s2 = append t (join T) ∧ lift_rel R s t ∧ lift_rel (lift_rel R) S T, ⟨nil, nil, S, T, by simp, by simp, by simp, h⟩, λ s1 s2 ⟨s, t, S, T, h1, h2, st, ST⟩, begin clear _fun_match _x, rw [h1, h2], rw [destruct_append, destruct_append], apply computation.lift_rel_bind _ _ (lift_rel_destruct st), exact λ o p h, match o, p, h with | some (a, s), some (b, t), ⟨h1, h2⟩ := by simp; exact ⟨h1, s, t, S, rfl, T, rfl, h2, ST⟩ | none, none, _ := begin dsimp [destruct_append.aux, computation.lift_rel], constructor, { intro, apply lift_rel_join.lem _ ST (λ _ _, id) }, { intros b mb, rw [←lift_rel_o.swap], apply lift_rel_join.lem (swap R), { rw [←lift_rel.swap R, ←lift_rel.swap], apply ST }, { rw [←lift_rel.swap R, ←lift_rel.swap (lift_rel R)], exact λ s1 s2 ⟨s, t, S, T, h1, h2, st, ST⟩, ⟨t, s, T, S, h2, h1, st, ST⟩ }, { exact mb } } end end end⟩ theorem join_congr {S T : wseq (wseq α)} (h : lift_rel equiv S T) : join S ~ join T := lift_rel_join _ h theorem lift_rel_bind {δ} (R : α → β → Prop) (S : γ → δ → Prop) {s1 : wseq α} {s2 : wseq β} {f1 : α → wseq γ} {f2 : β → wseq δ} (h1 : lift_rel R s1 s2) (h2 : ∀ {a b}, R a b → lift_rel S (f1 a) (f2 b)) : lift_rel S (bind s1 f1) (bind s2 f2) := lift_rel_join _ (lift_rel_map _ _ h1 @h2) theorem bind_congr {s1 s2 : wseq α} {f1 f2 : α → wseq β} (h1 : s1 ~ s2) (h2 : ∀ a, f1 a ~ f2 a) : bind s1 f1 ~ bind s2 f2 := lift_rel_bind _ _ h1 (λ a b h, by rw h; apply h2) @[simp] theorem join_ret (s : wseq α) : join (ret s) ~ s := by simp [ret]; apply think_equiv @[simp] theorem join_map_ret (s : wseq α) : join (map ret s) ~ s := begin refine ⟨λ s1 s2, join (map ret s2) = s1, rfl, _⟩, intros s' s h, rw ←h, apply lift_rel_rec (λ c1 c2, ∃ s, c1 = destruct (join (map ret s)) ∧ c2 = destruct s), { exact λ c1 c2 h, match c1, c2, h with | ._, ._, ⟨s, rfl, rfl⟩ := begin clear h _match, have : ∀ s, ∃ s' : wseq α, (map ret s).join.destruct = (map ret s').join.destruct ∧ destruct s = s'.destruct, from λ s, ⟨s, rfl, rfl⟩, apply s.cases_on _ (λ a s, _) (λ s, _); simp [ret, ret_mem, this, option.exists] end end }, { exact ⟨s, rfl, rfl⟩ } end @[simp] theorem join_append (S T : wseq (wseq α)) : join (append S T) ~ append (join S) (join T) := begin refine ⟨λ s1 s2, ∃ s S T, s1 = append s (join (append S T)) ∧ s2 = append s (append (join S) (join T)), ⟨nil, S, T, by simp, by simp⟩, _⟩, intros s1 s2 h, apply lift_rel_rec (λ c1 c2, ∃ (s : wseq α) S T, c1 = destruct (append s (join (append S T))) ∧ c2 = destruct (append s (append (join S) (join T)))) _ _ _ (let ⟨s, S, T, h1, h2⟩ := h in ⟨s, S, T, congr_arg destruct h1, congr_arg destruct h2⟩), intros c1 c2 h, exact match c1, c2, h with ._, ._, ⟨s, S, T, rfl, rfl⟩ := begin clear _match h h, apply wseq.cases_on s _ (λ a s, _) (λ s, _); simp, { apply wseq.cases_on S _ (λ s S, _) (λ S, _); simp, { apply wseq.cases_on T _ (λ s T, _) (λ T, _); simp, { refine ⟨s, nil, T, _, _⟩; simp }, { refine ⟨nil, nil, T, _, _⟩; simp } }, { exact ⟨s, S, T, rfl, rfl⟩ }, { refine ⟨nil, S, T, _, _⟩; simp } }, { exact ⟨s, S, T, rfl, rfl⟩ }, { exact ⟨s, S, T, rfl, rfl⟩ } end end end @[simp] theorem bind_ret (f : α → β) (s) : bind s (ret ∘ f) ~ map f s := begin dsimp [bind], change (λ x, ret (f x)) with (ret ∘ f), rw [map_comp], apply join_map_ret end @[simp] theorem ret_bind (a : α) (f : α → wseq β) : bind (ret a) f ~ f a := by simp [bind] @[simp] theorem map_join (f : α → β) (S) : map f (join S) = join (map (map f) S) := begin apply seq.eq_of_bisim (λ s1 s2, ∃ s S, s1 = append s (map f (join S)) ∧ s2 = append s (join (map (map f) S))), { intros s1 s2 h, exact match s1, s2, h with ._, ._, ⟨s, S, rfl, rfl⟩ := begin apply wseq.cases_on s _ (λ a s, _) (λ s, _); simp, { apply wseq.cases_on S _ (λ s S, _) (λ S, _); simp, { exact ⟨map f s, S, rfl, rfl⟩ }, { refine ⟨nil, S, _, _⟩; simp } }, { exact ⟨_, _, rfl, rfl⟩ }, { exact ⟨_, _, rfl, rfl⟩ } end end }, { refine ⟨nil, S, _, _⟩; simp } end @[simp] theorem join_join (SS : wseq (wseq (wseq α))) : join (join SS) ~ join (map join SS) := begin refine ⟨λ s1 s2, ∃ s S SS, s1 = append s (join (append S (join SS))) ∧ s2 = append s (append (join S) (join (map join SS))), ⟨nil, nil, SS, by simp, by simp⟩, _⟩, intros s1 s2 h, apply lift_rel_rec (λ c1 c2, ∃ s S SS, c1 = destruct (append s (join (append S (join SS)))) ∧ c2 = destruct (append s (append (join S) (join (map join SS))))) _ (destruct s1) (destruct s2) (let ⟨s, S, SS, h1, h2⟩ := h in ⟨s, S, SS, by simp [h1], by simp [h2]⟩), intros c1 c2 h, exact match c1, c2, h with ._, ._, ⟨s, S, SS, rfl, rfl⟩ := begin clear _match h h, apply wseq.cases_on s _ (λ a s, _) (λ s, _); simp, { apply wseq.cases_on S _ (λ s S, _) (λ S, _); simp, { apply wseq.cases_on SS _ (λ S SS, _) (λ SS, _); simp, { refine ⟨nil, S, SS, _, _⟩; simp }, { refine ⟨nil, nil, SS, _, _⟩; simp } }, { exact ⟨s, S, SS, rfl, rfl⟩ }, { refine ⟨nil, S, SS, _, _⟩; simp } }, { exact ⟨s, S, SS, rfl, rfl⟩ }, { exact ⟨s, S, SS, rfl, rfl⟩ } end end end @[simp] theorem bind_assoc (s : wseq α) (f : α → wseq β) (g : β → wseq γ) : bind (bind s f) g ~ bind s (λ (x : α), bind (f x) g) := begin simp [bind], rw [← map_comp f (map g), map_comp (map g ∘ f) join], apply join_join end instance : monad wseq := { map := @map, pure := @ret, bind := @bind } /- Unfortunately, wseq is not a lawful monad, because it does not satisfy the monad laws exactly, only up to sequence equivalence. Furthermore, even quotienting by the equivalence is not sufficient, because the join operation involves lists of quotient elements, with a lifted equivalence relation, and pure quotients cannot handle this type of construction. instance : is_lawful_monad wseq := { id_map := @map_id, bind_pure_comp_eq_map := @bind_ret, pure_bind := @ret_bind, bind_assoc := @bind_assoc } -/ end wseq